ENVIRONMENTAL EDUCATION: A POTENT TOOL FOR THE ATTAINMENT OF SUSTAINABLE DEVELOPMENT GOALS (GOOD HEALTH AND WELLBEING, CLEAN WATER AND SANITATION, AFFORDABLE AND CLEAN ENERGY AND SUSTAINABLE CITIES AND COMMUNITIES) IN SOUTH-SOUTH, NIGERIA - Onnoghen, Usang Nkanu , Ojong, Aganyi Asu , Omang, Theresa Nkim , Obibessong, Verampuon , Dr. (Mrs.) Asor Love Joseph (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research surveys knowledge base on core environmental issues and interests of randomly selected students of tertiary institutions in South South States in Nigeria. Several similar research shows minimal quantitative studies outlining approaches and the required components of Environmental Education ( EE) to achieve sustainable development objectives. Descriptive figures (simple percentage size, bar charts and pie charts) introduced into feedback and other analyses in print media. Results indicate a poor understanding of global challenges as well as local environmental ones. Consequently, a healthier globe with greater capacity can be reached as prospective decision makers. This paper offers an analysis with numerous programs on the role of environmental education in sustainable growth at global and regional level in particular. The paper further includes a concise overview of various environmental campaigns, training programs, and curriculum growth strategies to meet sustainability targets. The paper shows that environmental awareness is a powerful tool for achieving sustainable development goals; health and well-being, clean water and sanitation, accessible, clean energy and sustainable cities and communities as well. It would also help decision-makers design better strategies to implement environmental education properly in Nigeria and achieve the common sustainability goal. Moreover, the paper also draws attention to the relationship between environmental education and national sustainable development. We argue that environment and development are intertwined and therefore, in the collective bid to achieve sustainable development, systematically integrated into educational activities in order to produce environmentally responsible and responsible citizens and policies.